Pengaruh Edukasi Pre-Operasi terhadap Kecemasan Pasien Operasi Umum : Implementasi Program Pengabdian kepada Masyarakat di Rumah Sakit - Bayu Despriyanto Pratama; Galih Pria Pambayun (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Preoperative anxiety is a common issue experienced by patients before undergoing general surgery. This anxiety can negatively impact patients' physiological and psychological conditions and affect postoperative outcomes. A preoperative education program has been implemented as part of community service at the hospital to reduce patient anxiety. This study aims to evaluate the effect of preoperative education on the anxiety levels of patients undergoing general surgery. The method used is a quantitative approach with a pre-test and post-test design. The results show that preoperative education significantly reduces patients' anxiety levels before surgery. Thus, preoperative education can be an effective intervention to improve patients' mental preparedness before undergoing surgical procedures.